Toxicity of polyhalogenated dibenzo-p-furans in the light of nucleic acid bases interaction. (October 2018) - Sharma, Bhumika K.; Roy, Debesh R.
Graphical abstract: Highlights: Toxicity of series of polyhalogenated dibenzo- p -furans is explained significantly. A QSAR investigation employing Density Functional Theory is performed. Global Δ N and local f max + are developed as potential structural descriptors. Δ N is quantified as energy transfer between inhibitors and NA bases interactions. Developed QSAR model is validated successfully with about 90% efficacy. Abstract: Quantitative structure-activity relationship (QSAR) investigation utilizing quantum chemical descriptors under density functional theory is performed to predict the toxicity ( p EC50 ) of a series of polyhalogenated dibenzo- p -furans (PHDFs). PHDFs are very important concern to the researchers due to their presence and diverse effects in the environment. A successful two parameter QSAR model is developed with a combination of a global descriptor known as charge transfer (Δ N ) between toxins and biosystem and a local descriptor as Fukui function ( f max + ) for maximum nucleophilic attack at the toxin site. A systematic analysis is performed to identify the electron donation/acceptance nature of the considered PHDF compounds with the choice of a model biosystems comprising five different nucleic acid bases, namely Adenine, Thymine, Guanine, Cytosine and Uracil to identify proper Δ N descriptor. Accordingly, PHDFs are found to be electron acceptors with maximum charge transfer from Guanine and therefore, Δ N G is utilized as the charge transfer parameter for all the toxins in the present work. The selected combination of global and local descriptors (Δ N G and f max + ) are found to predict 93% of the observed toxicity ( p EC50 ) of the PHDFs. The developed QSAR model is tested for two different test sets: PHDFs and polyhalogenated biphenyls (PHBs) with about 90% of prediction of their toxicity values, which confirms the importance of the selected descriptors.